Treatment challenges in elderly diabetics - Kokoszka-Paszkot, Janina (Lekarz POZ, 2018)
In 2017 the proportion of people aged 65 years and over reached 14% of the total Polish population. Eurostat predicts that Poland will become one of the oldest European populations by 2060. 25–30% of the elderly are estimated to be affected by diabetes mellitus. Studies of elderly diabetics proved the efficacy and safety of DPP-4 inhibitors with minor hypoglycaemia risk, lack of fracture risk and weight gain, as well as neutral or even reduced cardiovascular complications and mortality. The studies’ results show DPP-4 to be an effective and safe alternative therapy for elderly diabetics with chronic kidney disease. Co-morbidities, especially chronic kidney disease, cognitive impairment, and frailty syndrome should be considered during therapy of elderly diabetics. Modern therapies (gliptins) seem to be a very interesting option in the elderly population.